Cold‐water immersion decreases cerebral oxygenation but improves recovery after intermittent‐sprint exercise in the heat. Issue 4 (4th March 2013) - Minett, G. M.; Duffield, R.; Billaut, F.; Cannon, J.; Portus, M. R.; Marino, F. E.
<x xml:space="preserve">Abstract</x> This study examined the effects of post‐exercise cooling on recovery of neuromuscular, physiological, and cerebral hemodynamic responses after intermittent‐sprint exercise in the heat. Nine participants underwent three post‐exercise recovery trials, including a control (CONT), mixed‐method cooling (MIX), and cold‐water immersion (10 °C; CWI). Voluntary force and activation were assessed simultaneously with cerebral oxygenation (near‐infrared spectroscopy) pre‐ and post‐exercise, post‐intervention, and 1‐h and 24‐h post‐exercise. Measures of heart rate, core temperature, skin temperature, muscle damage, and inflammation were also collected. Both cooling interventions reduced heart rate, core, and skin temperature post‐intervention (P < 0.05). CWI hastened the recovery of voluntary force by 12.7 ± 11.7% (mean ± SD) and 16.3 ± 10.5% 1‐h post‐exercise compared to MIX and CONT, respectively (P < 0.01). Voluntary force remained elevated by 16.1 ± 20.5% 24‐h post‐exercise after CWI compared to CONT (P < 0.05). Central activation was increased post‐intervention and 1‐h post‐exercise with CWI compared to CONT (P < 0.05), without differences between conditions 24‐h post‐exercise (P > 0.05). CWI reduced cerebral oxygenation compared to MIX and CONT post‐intervention (P < 0.01). Furthermore, cooling interventions reduced cortisol 1‐h post‐exercise (P < 0.01), although only CWI blunted creatine kinase 24‐h post‐exercise compared to CONT (P < 0.05). Accordingly, improvements in neuromuscular recovery after post‐exercise cooling appear to be disassociated with cerebral oxygenation, rather reflecting reductions in thermoregulatory demands to sustain force production.